Knowledge, Attitudes and Practices of Contraception among Afghan Refugee Women in Pakistan: A Cross-Sectional Study - Raheel, Hina; Karim, Mehtab S.; Saleem, Sarah; Bharwani, Sulaiman (PLOS ONE, 2012)
Background During the 1980s, approximately three million people migrated from Afghanistan to Pakistan and sought refuge in several cities including the city of Karachi. After the initial settlement of the refugees, the international organizations transitioned the health care of these refugees to the two local non-profit service agencies in Karachi. One of these agencies subsidized health care to the refugees under their care and the other agency encouraged the refugees under their care to utilize governmental and non-governmental private health resources at the disposal of general public. Our objective was to measure the effect of health subsidy on the uptake of contraception among Afghan refugee women and compare them to the group of Afghan women without such a subsidy. Methodology/Principal Findings A randomly selected group of 650 married Afghan women-325 women in each group-participated in a detailed survey regarding the knowledge, attitude and practices of family planning and contraceptive use. 90 percent of the women in the health subsidy group had had heard of family planning, compared to the 45 percent in the non-subsidized group. The use of contraceptives was greater than two-fold in the former versus the latter. Results of logistic regression analysis revealed that the refugee women who had had access to subsidized healthcare were significantly more likely to use the contraceptive methods with advancing age as compared to the women in the non-health subsidy group. The difference remained significant after adjusting for other variables. Conclusions/Significance Refugee women who are provided subsidized healthcare are more inclined to use contraceptives. It is therefore important that Afghan refugee women living elsewhere in Pakistan be provided healthcare subsidy, whereby their reproductive health indicators could improve with reduced fertility. We strongly encourage facilities introducing such subsidies to refugees in resource poor settings to assess the impact through similar inquiry.